2010
DOI: 10.1007/s00405-010-1395-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tumour stage, comorbidity and therapy on survival of laryngeal cancer patients: a systematic review and a meta-analysis

Abstract: Laryngeal cancer is the second most common cancer of the respiratory tract with a relative 5-year survival over all tumour sites in the USA (61.6%; SEER 2009), which is much better than other head and neck cancers. The aim of this paper is to review and summarise data on the survival of laryngeal cancer patients. Literature search was conducted to identify articles in PubMed up to June 2009. Thirty studies with different study aims including sufficient information on survival of laryngeal cancer patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
74
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(77 citation statements)
references
References 68 publications
(148 reference statements)
3
74
0
Order By: Relevance
“…aryngeal carcinoma (LC) is the second most common cancer of the respiratory tract, and the overall 5-year relative survival rate is approximately 64.2% (1,2). Treatments for laryngeal cancer include surgery, radiotherapy, chemotherapy, and biological agents, which can be used either individually or in combination (3,4).…”
mentioning
confidence: 99%
“…aryngeal carcinoma (LC) is the second most common cancer of the respiratory tract, and the overall 5-year relative survival rate is approximately 64.2% (1,2). Treatments for laryngeal cancer include surgery, radiotherapy, chemotherapy, and biological agents, which can be used either individually or in combination (3,4).…”
mentioning
confidence: 99%
“…Larynx cancer is the second most common malignancy of the respiratory tract and of all head and neck cancers [1,2], with glottic carcinoma the most common type [3]. To date the majority of research on voice outcomes following early glottic cancer (Tis-T2) has explored the impact of either radiotherapy or transoral laser microsurgery on voice quality and functional outcomes [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Lymph node metastasis is common in supraglottic carcinoma and is the main cause of mortality for these patients. It has been reported that the incidence of lymph node metastasis may be as high as 25-50% in supraglottic carcinoma (1). Current treatments, including surgical intervention, radiation therapy and chemotherapy, have a moderate effect on early-stage cases, but are less effective in more advanced cases.…”
Section: Introductionmentioning
confidence: 99%